(untitled) - Cheever, John (New York, 2009)
This volume, published to coincide with Blake Bailey’s groundbreaking biography, is the largest collection of Cheever’s stories ever published, and celebrates his indelible achievement by gathering the complete Stories of John Cheever (1978), as well as seven stories from The Way Some People Live and seven additional stories first published in periodicals between 1930 and 1953. Also included are several short essays on writers and writing, including a previously unpublished speech on Saul Bellow.
Keywords: Truyện ngắn, Mỹ,Short stories, American